SLC37A4‐CDG: Second patient. Issue 1 (6th January 2021) - Wilson, Matthew P.; Quelhas, Dulce; Leão‐Teles, Elisa; Sturiale, Luisa; Rymen, Daisy; Keldermans, Liesbeth; Race, Valérie; Souche, Erika; Rodrigues, Esmeralda; Campos, Teresa; Van Schaftingen, Emile; Foulquier, François; et al.
Abstract: Recently, a disorder caused by the heterozygous de novo c.1267C>T (p.R423*) substitution in SLC37A4 has been described. This causes mislocalization of the glucose‐6‐phosphate transporter to the Golgi leading to a congenital disorder of glycosylation type II (SLC37A4‐CDG). Only one patient has been reported showing liver disease that improved with age and mild dysmorphism. Here we report the second patient with a type II CDG caused by the same heterozygous de novo c.1267C>T (p.R423*) mutation thereby confirming the pathogenicity of this variant and expanding the clinical picture with type 1 diabetes, severe scoliosis, and membranoproliferative glomerulonephritis. Additional clinical and biochemical data provide further insight into the mechanism and prognosis of SLC37A4‐CDG.